Pemikiran Dakwah M Natsir - Sumanto, Edi (DAWUH : Islamic Communication Journal, 2021)
Among the da'wah actors in Indonesia, one of them is M. Natsir. He was a man who was persistent in breaking through the da'wah of Islam through bureaucratic obstacles and also through remote areas by sending preachers to these areas. The reality of the propagation of Islam in these areas is difficult to deny. In fact, in remote areas that were visited by the Indonesian Islamic Da'wah Council, there was a splash of Islamic grace and subsequently built various kinds of Islamic education and da'wah facilities. M. Natsir emphasized and hoped that the mission of the missionary was to continue the duties of the apostles and prophetsTheda'is as the invitees must place the object of the da'wah as guests must be respected. The consequence is that the preachers are asked to present language, a good attitude with full politeness to their guests. So with the awareness of course there are weaknesses and strengths that exist, giving rise to comfort as well as the joys and sorrows of the task that must be carried out, by the muballigh do not stop to train yourself, in order to obtain greater inner strength so as to arrive at a higher spiritual state and fitrah, thus bringing that glorious preaching, more fearful of Allah. M. Natsir's thoughts on the preaching of Islam contain the meaning of Islamic da'wah in lafdziyah or literal terms. That is, the preaching of Islam is not only by knowing the delivery of Islamic teachings, as "inviting" to the target of preaching in the position of receiving news about Islamic teachings. So, the da'is who are in charge of inviting and calling out to preach as guests who need to be respected. In this case, the da'i must be able to display a good attitude, especially in words and deeds, such as being full of politeness to the targets of preaching, which needs to be respected.